Role of Water Vapor Modulation From Multiple Pathways in the Occurrence of a Record‐Breaking Heavy Rainfall Event in China in 2021 - Zhiqiu Gao; Jianbin Zhang; Miao Yu; Zhizhao Liu; Ruoying Yin; Shaohui Zhou; Lian Zong; Guicai Ning; Xiaoze Xu; Yunqian Guo; Han Wei; Yuanjian Yang (Earth and Space Science, 2022)
Abstract Extreme torrential rainfall events are low‐probability events. A “China‐Record Extremely Heavy Rainfall” (CREHR) event with rain rate of 201.9 mm/hr occurred on 20 July in Zhengzhou in North China. Using high‐density meteorological observations, ERA5 reanalysis data, remote sensing data from China's FY‐4A satellite, and numerical simulation, we revealed that sufficient warm–humid airflows were continuously transported to the Zhengzhou area via multiple pathways that were mainly modulated by the large‐scale western Pacific subtropical high to the north along with the anomalies of the westerly belt and a meso‐scale binary typhoon system. At the local scale, under the combined action of the vertical circulation that caused low‐level convergence and high‐level divergence, and the rapid uplift of water vapor related to the blocking by mountainous terrain, this CREHR event was eventually triggered. Particularly, our present work shows the roles of both typhoon Cempaka and meso‐scale convective systems to south of Henan province can not be ignored, producing a strong super‐thick water vapor transport layer. The existence of the binary typhoon raises the level of uncertainty involved in the water vapor transport of this CREHR event.